2014
DOI: 10.7860/jcdr/2014/8050.4239
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Lifestyle Diseases in Elderly from a Rural Community of Guntur District of Andhra Pradesh

Abstract: A significant number of elderly are suffering with chronic illnesses even in rural areas. There is a need to highlight the medical and socio-economic problems that are being faced by the elderly people especially the women in India. Rural health programmes need to also put the health problems of the elderly on par with other health related issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Furthermore, illiterate women, being housewives and widowhood considers factors that can increase the burden of lifestyle disease, a cross-sectional study among 9,067 older adults in India aimed to identify the burden of lifestyle-related disease among older adults. The results of this study revealed that women are more likely to increase the burden of diseases that contribute to lifestyle than men (Nallapu and Sai, 2014). Also, a study by Chen et al (2018), among community-dwelling elders in Taiwan revealed that older adult females are better at choosing a healthy diet than males.…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, illiterate women, being housewives and widowhood considers factors that can increase the burden of lifestyle disease, a cross-sectional study among 9,067 older adults in India aimed to identify the burden of lifestyle-related disease among older adults. The results of this study revealed that women are more likely to increase the burden of diseases that contribute to lifestyle than men (Nallapu and Sai, 2014). Also, a study by Chen et al (2018), among community-dwelling elders in Taiwan revealed that older adult females are better at choosing a healthy diet than males.…”
Section: Resultsmentioning
confidence: 81%
“…These may be compounded by physical incapacity due to an exhaustive list of disabilities because of multiple medical problems of varying severity. [3][4][5][6][7][8][9][10][11][12][13] The cumulative effect of these may be much greater than any individual disease. The elderly who are living alone are likely to suffer more from both acute and chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…All these lead to social isolation, a feeling of loneliness and hopelessness. These may be compounded by physical incapacity due to an exhaustive list of disabilities because of multiple medical problems of varying severity . The cumulative effect of these may be much greater than any individual disease.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, people in villages tend to age faster as they have little knowledge of a healthy diet and physical therapy [15,16].…”
Section: Scenario For Dnr: Public Versus Private Hospitalsmentioning
confidence: 99%